India's Growth and Employment Patterns: A Four-decade Perspective (1983-2024) - Sharma, Alakh N; Mehta, Balwant Singh (Economic and Political Weekly, 2024)
The paper analyses the patterns and trends in the labour markets in India spanning over four decades from 1983 to 2024. It also examines the long-term trends in labour force participation rates with a focus on the recent surge in women's work participatio
Keywords: Employment Patterns; Indian Labour Market; India's Growth; Labour and Employment